2020
DOI: 10.3390/plants9091058
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis of Amino Acids and Health Beneficial Properties of Cantaloupe Varieties Grown in Six Locations in the United States

Abstract: Cantaloupe is a good dietary source of amino acids, including γ-aminobutyric acid (GABA), glutamine, and citrulline. However, the levels of these amino acids vary among different cantaloupe varieties grown in different locations. Understanding the variation in amino acid contents provides fundamentally important information for quality control and improving melon varieties. To examine this variation, we measured the amino acid contents in cantaloupes grown in six locations in the United States (Texas, Georgia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 86 publications
(112 reference statements)
0
13
0
Order By: Relevance
“…Some melon varieties (Syngenta) showed comparatively lower TPC from the FB assay, which may be influenced by other compounds that interfere with the detection of phenolic compounds (such as organic acids, sugars, and ascorbic acid). An analysis of beverages and grains obtained similar results, showing higher F–C value results compared to the FB value [ 31 ]. To further study, applications of the optimized assay we examined commercial juices and compared the total phenolic content measured by F–C and optimized FB methods.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Some melon varieties (Syngenta) showed comparatively lower TPC from the FB assay, which may be influenced by other compounds that interfere with the detection of phenolic compounds (such as organic acids, sugars, and ascorbic acid). An analysis of beverages and grains obtained similar results, showing higher F–C value results compared to the FB value [ 31 ]. To further study, applications of the optimized assay we examined commercial juices and compared the total phenolic content measured by F–C and optimized FB methods.…”
Section: Discussionmentioning
confidence: 87%
“…The ABTS assay involves the generation of ABTS chromophores by oxidation of ABTS with potassium persulfate; antioxidant compounds prevent the generation of these chromophores. Our results showed that scavenging activities recorded higher when evaluated using the ABTS assay than with the DPPH assay ( Figure 1 A,B), this may be due to the type of reaction mechanisms—hydrogen atom transfer and single electron transfer, respectively [ 31 ]. Moreover, factors like stereo selectivity of radicals or solubility of extracts in different systems affect the extracts capacity to react and quench the different radicals [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sucrose accumulates as the major sugar (~50%) during ripening, with lower levels of fructose and glucose [7]. Muskmelons also have a large number of bioactive compounds such as folic acid, vitamin A (β-carotene), vitamin C (ascorbic acid), L-citrulline (a non-essential amino acid), and micronutrient elements such as iron, magnesium, and potassium [5,8]. These phytonutrients have numerous health-promoting properties such as anti-inflammatory, analgesic, antioxidant, anticancer, diuretic, antimicrobial, and antidiabetic activities [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…I have received many excellent manuscripts that try to shed some light on the potential mechanism of action of antioxidants and also described the identification of new compounds, bringing to the collection nine articles [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ] and two reviews [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al [ 13 ] have performed a multivariate analysis of amino acids and health-benefiting properties of cantaloupe varieties grown in six locations in the United States as a dietary source of protein and amino acids. The variation in amino acid amount is an indicator for quality control, and the selection of melon varieties for a commercial purpose from different locations.…”
Section: Introductionmentioning
confidence: 99%